2007
DOI: 10.1038/ni1515
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of CTLA-4 by HIV-specific CD4+ T cells correlates with disease progression and defines a reversible immune dysfunction

Abstract: In progressive viral infection, antiviral T cell function is impaired by poorly understood mechanisms. Here we report that the inhibitory immunoregulatory receptor CTLA-4 was selectively upregulated in human immunodeficiency virus (HIV)-specific CD4(+) T cells but not CD8(+) T cells in all categories of HIV-infected subjects evaluated, with the exception of rare people able to control viremia in the absence of antiretroviral therapy. CTLA-4 expression correlated positively with disease progression and negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
521
3
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 478 publications
(555 citation statements)
references
References 46 publications
29
521
3
2
Order By: Relevance
“…Moreover, PD-1 blockade seems to reactivate effector T cells through the targeting of certain transcriptional factors (i.e., nuclear factor kappa-light-chainenhancer of activated B cells, interferon regulatory factors 1 and 2, orphan nuclear receptor NR4A1, and B-lymphocyte-induced maturation protein 1) that cause a reengagement of the effector mechanisms in the epigenome of exhausted T cells 59 . CTLA-4 has also been found to have a clear role in multiple chronic infections, including HBV, HCV, and HIV, and its inhibition can increase the function of pathogen-specific T cells 60,61 . Epigenetic and transcriptional mechanisms determine the functional plasticity of T cells to switch between their exhausted and effector states 62 , and so altering the transcriptional landscape-for example, by manipulating transcription-factor and gene-enhancer expression-and epigenetic landscape-for example, by manipulating the activity of histone-modifying methylation or demethylation enzymes, histone acetylases, and DNA demethylases-of adoptively transferred T cells may yield a more specific anti-tumor response than generalized PD-1 and CTLA-4 blockade.…”
Section: Autoimmune Consequencesmentioning
confidence: 99%
“…Moreover, PD-1 blockade seems to reactivate effector T cells through the targeting of certain transcriptional factors (i.e., nuclear factor kappa-light-chainenhancer of activated B cells, interferon regulatory factors 1 and 2, orphan nuclear receptor NR4A1, and B-lymphocyte-induced maturation protein 1) that cause a reengagement of the effector mechanisms in the epigenome of exhausted T cells 59 . CTLA-4 has also been found to have a clear role in multiple chronic infections, including HBV, HCV, and HIV, and its inhibition can increase the function of pathogen-specific T cells 60,61 . Epigenetic and transcriptional mechanisms determine the functional plasticity of T cells to switch between their exhausted and effector states 62 , and so altering the transcriptional landscape-for example, by manipulating transcription-factor and gene-enhancer expression-and epigenetic landscape-for example, by manipulating the activity of histone-modifying methylation or demethylation enzymes, histone acetylases, and DNA demethylases-of adoptively transferred T cells may yield a more specific anti-tumor response than generalized PD-1 and CTLA-4 blockade.…”
Section: Autoimmune Consequencesmentioning
confidence: 99%
“…In addition to these inhibitory receptors, it was demonstrated that a variety of other inhibitory receptors were expressed on exhausted CD8 + T cells in chronic virus infections, and the increased levels of expression were critically associated with the severity of infection and the lower functionality of CD8 + T cells (10). Although the precise inhibitory mechanisms of each individual pathway are unclear, some inhibitory receptors, such as Tim-3, LAG-3, and CTLA4, are known to negatively regulate CD8 + T cell function cooperatively with PD-1, because combined blockade of these inhibitory receptors, along with the PD-1/PD-L1 pathway, synergistically improved CD8 + T cell responses (10)(11)(12)(13). Based on the present observations, Ag-specific effector CD8 + T cells in FV-infected mice seemed to be undergoing unusually rapid and extremely severe exhaustion.…”
Section: Discussionmentioning
confidence: 99%
“…PD-1 has been identified as a major cell-surface inhibitory receptor capable of regulating CD8 + and CD4 + T cell exhaustion in mice, as well as in humans and nonhuman primates (50). Tim-3 and CTLA-4 were recently found to be overexpressed on HIV-and hepatitis C virus-specific CD8 + and CD4 + T cells and to act to suppress effector functions of activated T cells (11)(12)(13)51). Upregulation of LAG-3 was also shown to correlate with the impaired effector functions and exhaustion of CD8 + T cells (10,52,53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports demonstrated that PD-1 was significantly upregulated on virus-specific CD8 + T cells and that CTLA-4 was upregulated on HIV-specific CD4 + T cells during persistent viral infection; both PD-1 and CTLA-4 could negatively regulate T cell functionality (6,7,15). Similarly to CTLA-4 and PD-1, lymphocyte activation gene-3 (LAG-3), which is a natural high-affinity ligand for MHC class II (MHC II) molecules (16), was shown to play an inhibitory role in regulating T cell immune responses by several studies (17)(18)(19)(20)(21).…”
mentioning
confidence: 99%